THE TRIPARTITE ROLE OF THE PSYCHE IN RON WILLIAMSON’S CHARACTER IN JOHN GRISHAM’S THE INNOCENT MAN: MURDER AND INJUSTICE IN A SMALL TOWN NOVEL - Hafiz Naufal Anshoor; Singgih Daru Kuncara; Fatimah Muhajir (Prosiding Seminar Nasional Bahasa, Sastra, dan Seni (Sesanti), 2021)
Psychoanalysis is the study to analyze the human's behavior and personality. It is one of the scientific disciplines developed by Sigmund Freud. It appears to scrutinize deeper of human personality. The tripartite psyche refers to id, ego, and superego. It exists to construct human’s personality based from the experiences. The role of id, ego, and superego are to maintain or balance human’s behavior. This thesis discusses about the tripartite role of the psyche in the main character in John Grisham’s The Innocent Man: Murder and Injustice in a Small Town novel named Ron Williamson. The purpose of this thesis is to investigate Ron Williamson’s tripartite psyche portrayed in the novel. The researcher used qualitative research methodology and psychoanalysis approach. The results of this thesis Ron Williamson, as the main character is a unique character. The Id of Ron Williamson depicted in the novel are immoral, uncontrollable, unethical, troublemaker, selfish, drunk, childish, excessive, erratic, unpredictable, hallucination, disoriented, mood swings, uncertain, delusional, and confused. In the other hand, the ego of Ron Williamson are worried, regret, reduce the selfishness, responsible, mindful, slowly unconfused, reduced the troublemaker, honest, patience, and rational thinking. The last is superego of Ron Williamson are polite, good attitudes, servant of God, sympathetic, stable behavior, intelligent, more sensible thinking, more responsive to his surroundings, devout Christian, quit from troublemaker, break out from selfishness, and forgiving. Furthermore, the findings show that those depictions are from conflicts to other minor character, self-conflict, direct description from the author, dialogues, and events in each chapter.